2-D Model of a H2/Br2 Flow Battery with Flow-Through Positive Electrode. Issue 3 (1st January 2016) - You, Xin; Ye, Qiang; Van Nguyen, Trung; Cheng, Ping
Abstract : A 2-D steady state model was developed to investigate the impact of positive electrode thickness on the performance of a hydrogen-bromine flow battery (HBFB). With this model, the voltage loss is resolved into activation, ohmic and mass transport parts, which provides quantitative assessment of the effect of electrode thickness on the cell performance. Since hydrogen bromide solution serves as both reactant/product and supporting electrolyte, the ionic conductivity varies with the change of state-of-charge (SOC), which in turn affect the trade-off among activation, ohmic and mass transport loss. The impact of electrode thickness on mass transport is also complicated due to the variable distributions of local current and reactant concentration at different operating conditions. Since thinner electrode appeals for stringent mass transport rate in pore scale while thicker electrode leads to appreciable mismatch in the distribution between reactant concentration and reaction rate, the optimal electrode thickness are suggested to be in the range of 2–3 mm on the positive side in a HBFB.